2015
DOI: 10.1016/j.rbmo.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Two protocols to treat thin endometrium with granulocyte colony-stimulating factor during frozen embryo transfer cycles

Abstract: The efficacy of two granulocyte colony-stimulating factor (G-CSF) protocols for thin endometrium were investigated. Eighty-two patients were diagnosed with thin endometrium (<7 mm). Thirty patients with previously cancelled embryo transfers received intrauterine G-CSF in subsequent frozen embryo transfer (FET) cycles. Patients were divided into the G-CSF only and G-CSF with endometrial scratch subgroups. Compared with previous cycles, endometrial thickness increased from 5.7 ± 0.7 mm to 8.1 ± 2.1 mm after G-CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 36 publications
2
72
0
Order By: Relevance
“…Since then, several studies with controversial results have evaluated the effect of GCSF on endometrial thickness and IVF success (Scarpellini & Sbracia 2012, Gleicher et al 2013, Barad et al 2014, Eftekhar et al 2014, Kunicki et al 2014, Li et al 2014, Xu et al 2015. In the studies of Scarpellini and coworkers and Xu and coworkers, the implantation and pregnancy rates were significantly higher in IVF patients treated with GCSF (Scarpellini & Sbracia 2012, Xu et al 2015, whereas in the studies of Barad and coworkers and Li and coworkers, treatment with GCSF did not affect endometrial thickness, implantation, or pregnancy rates in IVF patients (Barad et al 2014, Li et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies with controversial results have evaluated the effect of GCSF on endometrial thickness and IVF success (Scarpellini & Sbracia 2012, Gleicher et al 2013, Barad et al 2014, Eftekhar et al 2014, Kunicki et al 2014, Li et al 2014, Xu et al 2015. In the studies of Scarpellini and coworkers and Xu and coworkers, the implantation and pregnancy rates were significantly higher in IVF patients treated with GCSF (Scarpellini & Sbracia 2012, Xu et al 2015, whereas in the studies of Barad and coworkers and Li and coworkers, treatment with GCSF did not affect endometrial thickness, implantation, or pregnancy rates in IVF patients (Barad et al 2014, Li et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the similar results of Xu et al, our latest metaanalysis was conducted to investigate the effect of G-CSF on pregnant outcomes with six studies and 607 participants involved [1,7]. These results indicated that G-CSF might have the capacity to improve pregnancy outcomes, especially for patients with the thin endometrium or repeated IVF failure.…”
mentioning
confidence: 81%
“…However, for patients with thin endometrium, the production of G-CSF was influenced by abnormal function of endometrium and the mechanism for affecting the implantation should be further explored. For endometrial thickness, the studies by Xu et al and Li et al did not perform subgroup analyses according to pregnancy outcome, even though none of them detected the difference [1,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 82 women who had previously canceled cycles, 30 received G-CSF. 37 This group was further subdivided into two groups-one received G-CSF only and second group underwent endometrial scratching along with G-CSF. The remaining 50 women served as a control.…”
Section: Recombinant G-csf For Treatment Of Thin Endometrium In Art: mentioning
confidence: 99%